Factors Related to Lung Function Disorders in Workers at The Printing Area of PT X - Rizqiana Fauziyyah; Suhartono Suhartono; Nurjazuli Nurjazuli (Postgraduate, University of Mataram, 2025)
The use of chemicals in industry has benefits and negative impacts that follow. Solvent chemicals in the printing area of PT X are used to wash screen printing. One of the impacts of chemical use is the occurrence of impaired lung function in workers. The purpose of this study was to determine the factors associated with impaired lung function in workers in the printing area of PT X. This study is an observational study with a Cross Sectional approach. The population in this study was 84 workers in the printing area of PT X, with a total sample of 70 workers who have had a working period of more than 1 year. Data analysis was carried out by univariate and bivariate analysis using the Chi Square test. The results of this study indicate that there is a relationship between the habit of using PPE and impaired lung function in workers in the printing area of PT X (p value = 0.028), and shows no relationship between length of service (p value = 0.949), nutritional status (p value = 0.688), smoking intensity (p value = 0.967), exercise habits (p value = 0.957) with impaired lung function in workers in the printing area of PT X. Therefore, supervision through inspections and internal audits is needed in the implementation of occupational safety and health, especially in terms of the use of masks to prevent chemicals from entering the body.